Antecedents of Religiosity, Demographics, and Socio-Cultural to Succeed Woman’s Entrepreneur Empowerment and Welfare through Productive Zakat - Ahmad Ajib Ridlwan; A'rasy Fahrullah; Khusnul Fikriyah; Ach. Yasin; Aulia Siska Puspita Dewi (Falah: Jurnal Ekonomi Syariah, 2022)
This study aims to analyze the impact of religiosity, demography, and socio-cultural on the success of empowerment to the welfare woman enterpreneur. The data analysis technique uses the Structural Equation Model (SEM) approach. The analytical method used was Partial Least Square (PLS). Data source Obtained by distributing online questionnaires to 107 woman entrepreneur whose receive productive zakat through google forms. Based on the results of the study, religiosity, socio-cultural had a positive and significant influence on the success of empowering woman entrepreneurs who receive productive zakat. This shows that the higher level of religiosity and socio-cultural, the higher success in empowering women entrepreneurs who receive productive zakat. In contrast, demographics variable had no effect on the success of empowering women entrepreneurs. The results of this study will contribute to enrich the discourse of welfare empowerment, especially in productive zakat.